2020
DOI: 10.1007/s11019-020-09951-6
|View full text |Cite
|
Sign up to set email alerts
|

Medical conspiracy theories: cognitive science and implications for ethics

Abstract: Although recent trends in politics and media make it appear that conspiracy theories are on the rise, in fact they have always been present, probably because they are sustained by natural dispositions of the human brain. This is also the case with medical conspiracy theories. This article reviews some of the most notorious health-related conspiracy theories. It then approaches the reasons why people believe these theories, using concepts from cognitive science. On the basis of that knowledge, the article makes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 101 publications
(72 reference statements)
0
48
1
2
Order By: Relevance
“…Most conspiracy theories are not based on credible evidence but rather on inaccurate thoughts and frequently illogical ones. Psychotic experiences enhance the development of these types of thoughts [27,29,60]. For instance, Barron et al [61] suggested that there are positive and direct correlations between the belief in conspiracy theories and schizotypy domains, namely strange beliefs, magical thinking, and reference ideas [28,41,62,63].…”
Section: Discussionmentioning
confidence: 99%
“…Most conspiracy theories are not based on credible evidence but rather on inaccurate thoughts and frequently illogical ones. Psychotic experiences enhance the development of these types of thoughts [27,29,60]. For instance, Barron et al [61] suggested that there are positive and direct correlations between the belief in conspiracy theories and schizotypy domains, namely strange beliefs, magical thinking, and reference ideas [28,41,62,63].…”
Section: Discussionmentioning
confidence: 99%
“…Health-specific conspiracy theory beliefs have been cited as a facet of medical mistrust [ 31 ]. These conspiracy theories are characterized by the belief that medical organizations or the government is planning to do something harmful to certain groups [ 15 , 50 ]. For example, during the HIV/AIDS pandemic, conspiracy theories suggested the virus was invented to kill Black communities [ 51 ].…”
Section: Race Discrimination and Medical Mistrustmentioning
confidence: 99%
“…Anti-vaccination rhetoric and conspiracies are not new. They existed since Edward Jenner's time, when some rumors claimed that vaccination will make people grow horns [50,51]. The themes have been strikingly similar across time, and include distrust of the medical establishment or governments mandating vaccination; revulsion at the idea of introducing unknown substances into the body; accusations that the ingredients are harmful; or suspicion that the real motives behind vaccines are to make people sick or to control the population.…”
Section: September 28 2020mentioning
confidence: 99%